Pengaruh Kredibilitas Raditya Dika terhadap Citra Merek Bibit - Tasya, Tasya; Tamburian, H. H. Daniel (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Digital investment trends are increasingly in demand by millennials who are new to financial literacy. Bibit are here to help novice investors who just want to start investing. Bibit, which was built in 2019, has become the most downloaded mutual fund investment application on the Apps Store and Google Play with 1 million downloads in 2020. The formation of the Bibit brand image as the best and most trusted mutual fund investment application is carried out by using a brand ambassador. Bibit chose Raditya Dika to be the brand ambassador for the Bibit application. The credibility of a Raditya Dika is believed to be able to influence the public's perception of the Bibit brand image. This study examines the influence of Raditya Dika's credibility on the brand image of Bibit. The purpose of this quantitative research is to find out the influence of Raditya Dika's credibility on the Brand Image of Bibit through a survey method. The population used is 100 millennial generation respondents who are Instagram followers and Bibit users. The results found by the researchers stated that Raditya Dika's credibility on the brand image of Bibit had a significant influence. Tren investasi digital semakin diminati oleh generasi milenial yang baru melek finansial. Bibit hadir untuk membantu investor pemula yang baru ingin memulai investasi tersebut. Bibit yang dibangun pada tahun 2019 menjadi aplikasi investasi reksadana paling banyak diunduh di Apps Store dan Google Play sebanyak satu juta pengunduh pada tahun 2020. Pembentukan citra merek Bibit sebagai aplikasi investasi reksadana terbaik dan terpercaya dilakukan dengan pemanfaatan brand ambassador. Bibit memilih Raditya Dika menjadi brand ambassador aplikasi Bibit. Kredibilitas seorang Raditya Dika dipercayai dapat mempengaruhi persepsi masyarakat terhadap citra merek Bibit. Penelitian ini meneliti pengaruh kredibilitas Raditya Dika terhadap Citra Merek Bibit. Tujuan penelitian kuantitatif ini adalah mencari pengaruh kredibilitas Raditya Dika terhadap Citra Merek Bibit melalui metode survei. Populasi yang digunakan yaitu 100 responden generasi milenial yang menjadi pengikut Instagram dan pengguna Bibit. Hasil penelitian menunjukkan bahwa kredibilitas Raditya Dika memengaruhi citra merek Bibit memiliki pengaruh yang signifikan.